JAMINAN SOSIAL BAGI PEKERJA DI SEKTOR INFORMAL SEBAGAI WUJUD PELAKSANAAN SILA KELIMA UUD NRI 1945 - Rahmanda Putra, I Gusti Ngurah Brama Abimayu; Westra, I Ketut (Kertha Desa; Vol 9 No 3 (2021), 2021)
Studi ini memiliki tujuan guna memberikan dengan pengetahuan terkait perlindungan jaminan sosial pekerja informal dalam menghadapi guncangan ekonomi, kemudian guna memberikan tujuan pemahaman mekanisme penyelenggaraan program jaminan sosial bagi pekerja informal. Hasil studi nenunjukkan perlindungan jaminan sosial bagi pekerja sektor informal dilaksanakan melalui Jaminan Sosial Nasional berdasarkan UU No. 40/2004 dan UU No. 24/2011 tentang BPJS. Perlindungan jaminan sosial bagi pekerja di sektor informal diselenggarakan melalui BPJS Ketenagakerjaan dengan sistem asuransi sosial. Usaha perlindungan sosial dari pemerintah bagi pekerja informal saat terjadi guncangan ekonomi dilaksanakan stimulus berkenaan pelaku usaha tidak melalukan PHK karyawan dan memberikan keringan relaksasi iuran BPJS, bantuan sosial bagi pekerja informal kategori miskin, dan beberapa kemudahan lain yang diberikan pemerintah bagi para pekerja agar keadaan ekonomi tidak semakin terpuruk. Mekanisme penyelenggaraan program jaminan sosial bagi pekerja informal dilaksanakan secara mandiri maupun melalui anggota bukan penerima upah. Peserta diberikan pilihan cara mendaftar dikantor BPJS atau secara online melalui website resmi BPJS. Program jaminan social wajib bagi pekerja informal yaitu Jaminan JKK dan JKM. Sedangkan JHT adalah jaminan tidak wajib bagi pekerja informal. Kata Kunci: Jaminan Sosial Pekerja, Pekerja Sektor Informal   ABSTRACT This study aims to provide knowledge related to social security protection for informal workers in the face of economic shocks, then to provide an understanding of the mechanism for implementing social security programs for informal workers. The study results show that social security protection for informal sector workers is implemented through the National Social Security based on Law no. 40/2004 and Law no. 24/2011 on BPJS. Social security protection for workers in the informal sector is provided through BPJS Ketenagakerjaan with a social insurance system. Social protection efforts from the government for informal workers when an economic shock occurs, a stimulus is implemented regarding business actors not laying off employees and providing relief from BPJS contribution relaxation, social assistance for informal workers in the poor category, and several other facilities provided by the government for workers so that the economic situation does not increase worse off. The mechanism for administering social security programs for informal workers is carried out independently or through non-wage members. Participants are given the choice of how to register at the BPJS office or online through the official BPJS website. Mandatory social security programs for informal workers are JKK and JKM guarantees. Meanwhile, JHT is a non-mandatory guarantee for informal workers. Key Words: Social Security Workers, Informal Sector Workers